FLASHCARD AS A MEDIA TO IMPROVE STUDENTSâ€™ WRITING SKILL IN DESCRIPTIVE PARAGRAPH - Musyaffa', M. Lathif (E-Link Journal, 2020)
The main purpose of this research is to know the improvement of studentsâ€™ writing skill in descriptive paragraph through flashcard media. This research was conducted at SMP â€œEmpat Limaâ€ Karanggeneng. This research is a classroom action research which consisted of two cycles. This study was carried out on February until May 2020. The subjects were the seventh grade students of SMP â€œEmpat Limaâ€ Karanggeneng, Lamongan. The data were collected by holding the test, interviewing, observing and distributing the questionnaire. The instruments that have been used are writing paragraph rubric, interview guideline, observational note and questionnaire sheet. The data that were used in this research are qualitative dan quantitative. This study used democratic validity, outcome validity, catalytical validity, process validity and dialogic validity as the validation. Then, the reliability of this study were time and investigator triangulation. There were several steps in this research implememntation, they are identifying the problems, planning, acting, observing and reflecting. The results showed that the use flashcard media in writing has been able to improve studentsâ€™ writing skill. According to the qualitative data, the students were enjoy and enthusiastic with the implementation of flahcard media in writing lesson. The They also felt easier to make a descriptive paragraph through this media. According to the quantitative data, the studentsâ€™ main score was improved in the each cycle.Â Keywords: : Flashcard, writing skill